2020
DOI: 10.1021/acsomega.0c00098
|View full text |Cite
|
Sign up to set email alerts
|

Cane Molasses Graphene Quantum Dots Passivated by PEG Functionalization for Detection of Metal Ions

Abstract: Poly(ethylene glycol) passivated graphene quantum dots (PEG-GQDs) were synthesized based on a green and effective strategy of the hydrothermal treatment of cane molasses. The prepared PEG-GQDs, with an average size of 2.5 nm, exhibit a brighter blue fluorescence and a higher quantum yield (QY) (up to approximately 21.32%) than the QY of GQDs without surface passivation (QY = 10.44%). The PEG-GQDs can be used to detect and quantify paramagnetic transition-metal ions including Fe 3+ , Cu 2+ , Co 2+ , Ni 2+ , Pb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 40 publications
(55 reference statements)
2
30
0
Order By: Relevance
“…[ 29 ] prepared nitrogen‐doped GQDs and fluorine‐doped GQDs from plant leaves as carbon sources with a QY of 41.2% and 38.9%, respectively. Our group [ 30 ] prepared cane molasses GQDs and modified their surface defects with polyethene glycol, the QY was twice as high as that of the unpassivated GQDs. These examples show that the heteroatom doping or surface modification can improve the QY of carbon dots to some extent.…”
Section: Carbon Source and Synthesis Methods Of Biomass Carbon Dotsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 29 ] prepared nitrogen‐doped GQDs and fluorine‐doped GQDs from plant leaves as carbon sources with a QY of 41.2% and 38.9%, respectively. Our group [ 30 ] prepared cane molasses GQDs and modified their surface defects with polyethene glycol, the QY was twice as high as that of the unpassivated GQDs. These examples show that the heteroatom doping or surface modification can improve the QY of carbon dots to some extent.…”
Section: Carbon Source and Synthesis Methods Of Biomass Carbon Dotsmentioning
confidence: 99%
“…Besides, the QY of 5 nm CQDs prepared from Chinese ink [ 53 ] could reach as high as 78%. Similarly, uniformly distributed carbon dots could also be produced by using sugarcane bagasse pulp [ 54 ] and cane molasses [ 30 ] as carbon sources. Industrial solid waste accounts for a significant part of municipal waste and the reports about coal, coke, and asphalt are common.…”
Section: Carbon Source and Synthesis Methods Of Biomass Carbon Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, they observed that stem cell osteogenesis was augmented by GQDs but decreased when the cells were treated with GO. Some studies have been reported on the use of PEGylated GQDs for bioimaging, 57 detection of metal ions, 58 and cancer therapy, 59 etc. However, there is little reported information on the interaction of PEGylated GQDs with stem cells.…”
Section: Interaction With Stem Cellsmentioning
confidence: 99%
“…In recent years, the use of carbon materials and nanoscale spherical TiO 2 composite to improve their photocatalytic activity has become a research hotspot. [ 184,185 ] Carbon materials not only have high electrical conductivity, [ 186 ] large specific surface area, [ 187 ] and so on, but also have a variety of structures (activated carbon, [ 188–190 ] graphene, [ 191–193 ] carbon quantum dots [ 194–197 ] (CQDs), and so on), so the composite of TiO 2 and carbon materials is beneficial to reduce the photogenerated carriers recombination rate; thus, improving the photocatalytic activity of spherical TiO 2.…”
Section: Different Types Of Nanoscale Spherical Tio2 Modificationmentioning
confidence: 99%